Ongoing evolution of response assessment in glioma: Where do we stand? - Li Yi; Haolang Ming; Shengping Yu; Bingcheng Ren; Xuejun Yang (Glioma, 2018)
The investigation and development of recently introduced agents or radiological measurements caused emergent misunderstandings to the response assessment of glioma. To date, the classical Macdonald criteria and the response assessment of neuro-oncology (RANO) criteria have been used successively for the evaluation of glioma outcome. However, ongoing efforts on complementary assessments are necessary to combat this malignancy. In this review, we highlight the shortcomings of the current criteria and introduce the initiative effort of RANO guideline and its offspring. We also discuss some future barriers for accurate assessment of treatment response in glioma.